2019
DOI: 10.1080/14767058.2018.1509068
|View full text |Cite
|
Sign up to set email alerts
|

The role of cervical pessary and progesterone therapy in the phenomenon of placenta previa migration

Abstract: The use of the Arabin cervical pessary combined with progesterone in patients with placenta previa significantly reduced the rate of preterm delivery < 34 weeks and bleeding during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Another area in which pessaries have recently been used is in the prevention of pre-term births. Studies are currently examining the efficacy of cervical pessaries with and without vaginal progesterone in women with placenta praevia, short cervix or twin gestation [219,220].…”
Section: Future Directionsmentioning
confidence: 99%
“…Another area in which pessaries have recently been used is in the prevention of pre-term births. Studies are currently examining the efficacy of cervical pessaries with and without vaginal progesterone in women with placenta praevia, short cervix or twin gestation [219,220].…”
Section: Future Directionsmentioning
confidence: 99%
“…26 27 28 30 Our findings are similar to the single previous study evaluating the role of CP as a preterm birth prevention strategy, in that cervical cup pessary placement in women with a complete previa is associated with a reduction in admissions for vaginal bleeding leading to delivery. 32 In our study, the number of antepartum admissions for bleeding was twofold higher in women randomized to the EM group.…”
Section: Discussionmentioning
confidence: 44%
“…A recent randomized trial using a dome silicone pessary with vaginal progesterone in women with previa demonstrated that women in the pessary group were threefold less likely to experience vaginal bleeding prior to delivery and were less likely to deliver prior to 34 weeks' gestation. 32…”
mentioning
confidence: 99%
“…Of 16 studies, 12 studies [ 8 , 10 12 , 18 – 22 , 25 27 ] involved women with a singleton pregnancy and the other four [ 9 , 17 , 24 , 27 ] included women with multiple pregnancies. Five RCT [ 10 12 , 19 , 25 ] and four non-RCT [ 18 , 21 , 26 , 27 ] singleton studies included a control group receiving treatment with vaginal progesterone alone; two non-RCT singleton studies compared with a group receiving the combination of cervical cerclage and vaginal progesterone [ 18 , 20 ]; only one non-RCT singleton study used the group receiving vaginal progesterone + cervical cerclage + cervical pessary [ 18 ], tocolysis (ritodrine hydrochloride and magnesium sulfate) [ 22 ] or cervical pessary alone [ 8 ] as the control, respectively. Two non-RCT [ 9 , 23 ] multiple pregnancy studies included a control group receiving vaginal progesterone alone treatment; only one non-RCT multiple pregnancy used the group receiving conservative treatment [ 24 ] or no treatment [ 17 ] as the control, respectively.…”
Section: Resultsmentioning
confidence: 99%